The Knowledge of Nurses in Pain Management and Use of Non-Drug Methods and Associated Factors - Çetinkaya, Şenay; Yüksel, Hümeyra (Jour Med Resh and Health Sci, 2023)
Objective: The study was carried out as a cross-sectional study in order to examine the nurses' pain management and the use of non-drug methods in terms of the factors like educational level, clinics where nurses worked, and working durations, which affect these. Methods: The research was conducted by surveys with 169 nurses working in the Internal-Surgical and Intensive Care Unit of Mersin University Health Research and Application Center in September and October 2018. The personal information form, the Knowledge and Behavioral Scale of Nurses Pain and Non-Drug Methods Form were used to collect the data. Results: The mean age of the nurses who participated in the present study was 29.72±5.54 (years), and the mean working time was 6.62±5.36 years. It was determined that the nurses knew hot-cold treatment, massage, nutritional treatment and music listening methods among non-drug methods at the highest level. In pain management 88(52.1%) were found to use pharmacological and non-pharmacological methods. The pain information of the nurses, attitude survey, high school graduates 5.46±1.88 and 5.99±2.41 points of the graduate nurses were found to be close to the average of the average score. There was no statistically significant difference between the knowledge scores and education level of the nurses about the pain and the duration of the study (p>0.05). Conclusion: As a result, it was determined that nurses did not have sufficient knowledge about pain diagnosis and knowledge of non-pharmacological management of pain. The pain-related interventions must not be limited with pharmacological methods, and the use of non-pharmacological applications must be encouraged.